Labor Migration System (On the Example of Uzbekistan) (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses the legal regulation of relations in the field of migration. A fund has been set up to support individuals working abroad and to protect their rights and interests. The practice of insuring the lives and health of migrant workers and allocating mortgage loans for their family members has been introduced. It is impossible to solve these important tasks without accurate information on the factors, directions and results of external labor migration and the labor resources involved in it.